2003
DOI: 10.1111/j.1349-7006.2003.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate predictive markers of anticancer drug sensitivity using a panel of human cancer cell lines

Abstract: We previously investigated the correlations between the expression of 9216 genes and various chemosensitivities in a panel of 39 human cancer cell lines 1) and found that the expression levels of AKR1B1 and CTSH were correlated with sensitivity and resistance to multiple drugs, respectively. To validate these correlations, we investigated the expression of these two genes and the chemosensitivities in 12 additional gastric cancer cell lines. The expression of AKR1B1 in the additional cell lines exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Only AKR1B1 expression has a significant association with clinical outcome, being associated with reduced survival in acute myeloid leukemias and multiple myeloma (Figure 3). Recent reports have implicated AKRs in cellular responses to various stresses, including promotion of hypoxia-driven HIF1a signaling, inflammation, and resistance to chemotherapeutics (Dan et al, 2003; Plebuch et al, 2007; Yadav et al, 2007, 2009, 2011; Matsunaga et al, 2011; Zhong et al, 2011). AKR1B1 over-expression has also been associated with an EMT-like phenotype, is implicated in colon carcinogenesis, and notably, increased AKR1B1 protein expression and enzymatic activity has been reported in several cancer types (Saraswat et al, 2006; Tammali et al, 2009, 2011a,b; Ramana et al, 2010; Zablocki et al, 2011), further suggesting that AKRs play a functional role in tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only AKR1B1 expression has a significant association with clinical outcome, being associated with reduced survival in acute myeloid leukemias and multiple myeloma (Figure 3). Recent reports have implicated AKRs in cellular responses to various stresses, including promotion of hypoxia-driven HIF1a signaling, inflammation, and resistance to chemotherapeutics (Dan et al, 2003; Plebuch et al, 2007; Yadav et al, 2007, 2009, 2011; Matsunaga et al, 2011; Zhong et al, 2011). AKR1B1 over-expression has also been associated with an EMT-like phenotype, is implicated in colon carcinogenesis, and notably, increased AKR1B1 protein expression and enzymatic activity has been reported in several cancer types (Saraswat et al, 2006; Tammali et al, 2009, 2011a,b; Ramana et al, 2010; Zablocki et al, 2011), further suggesting that AKRs play a functional role in tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of new therapeutic targets and development of novel cancer therapies is still a pressing need. Previous studies have shown that the human aldo-ketoreductase AKR1B10 is over-expressed in cancers of the liver and lungs (Fukumoto et al, 2005; Woenckhaus et al, 2006; Heringlake et al, 2010; Kang et al, 2011; Schmitz et al, 2011) while AKR1B10 and the related enzyme AKR1B1 are both linked to drug resistance in cancer-derived cell lines (Dan et al, 2003; Plebuch et al, 2007; Matsunaga et al, 2011; Zhong et al, 2011). Several published studies have also pointed to role for AKR1B1 in colon carcinogenesis (Tammali et al, 2009, 2011a,b; Ramana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting TKT has been demonstrated to lead to increased oxidative stress, causing increased sensitivity of cancer cells to therapeutic treatments, including Sorafenib ( 29 ). ATP binding cassette subfamily C member 1 ( 30 ), integrin subunit β1 (ITGB1) ( 31 , 32 ) and aldo-keto reductase family 1 member B ( 33 , 34 ) have been reported to be involved in chemoresistance/radioresistance and cancer metastasis. P21-activated kinase 2 ( 35 ), G protein nucleolar 3 ( 36 ), nucleophosmin ( 37 ) and pericentriolar material 1 ( 38 ) have been associated with metastatic characteristics in various types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Results from the NCI60 panel were also observed in other cell line panels, e.g. the classification of drugs based on their modes of action [ 218 ]. Based on these results, Nakatsu et al complemented the JFCR-39 cell line panel and developed an integrated database of chemosensitivity correlated with gene expression for this new cell line panel, called JFCR-45.…”
Section: Genomicsmentioning
confidence: 87%